2022
DOI: 10.1002/jwmg.22162
|View full text |Cite
|
Sign up to set email alerts
|

Finding fishers: determining fisher occupancy in the Northern Rocky Mountains

Abstract: Monitoring rare and elusive carnivores is inherently challenging because they often occur at low densities and require more resources to effectively assess status and trend. The fisher (Pekania pennanti) is an elusive mesocarnivore endemic to North America; in its western populations it is classified as a species of greatest conservation need. During winter of 2018-2019, we deployed remotely triggered cameras in randomly selected, spatially balanced 7.5-km × 7.5-km grid cells across a broad study area in weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Previous studies found no difference in detection probabilities for wolverines (Lukacs et al., 2020) or fishers (Krohner et al., 2022, using portions of the same data analyzed here) at CT stations paired with automated scent dispensers per our protocol versus those regularly replenished with meat baits and scent lures. These findings, in combination with cost savings and reduced risks associated with not having to visit survey stations in winter, led to the widespread application of our survey protocol for wolverine surveys conducted during winter 2021/22 in Montana, Idaho, Wyoming, Colorado, Utah, Oregon, and Washington, and for fisher surveys conducted during winter 2023/24 across Idaho and Washington (C. Mosby [Idaho Fish and Game], J. Lewis [Washington Fish and Wildlife], pers.…”
Section: Discussionmentioning
confidence: 42%
See 4 more Smart Citations
“…Previous studies found no difference in detection probabilities for wolverines (Lukacs et al., 2020) or fishers (Krohner et al., 2022, using portions of the same data analyzed here) at CT stations paired with automated scent dispensers per our protocol versus those regularly replenished with meat baits and scent lures. These findings, in combination with cost savings and reduced risks associated with not having to visit survey stations in winter, led to the widespread application of our survey protocol for wolverine surveys conducted during winter 2021/22 in Montana, Idaho, Wyoming, Colorado, Utah, Oregon, and Washington, and for fisher surveys conducted during winter 2023/24 across Idaho and Washington (C. Mosby [Idaho Fish and Game], J. Lewis [Washington Fish and Wildlife], pers.…”
Section: Discussionmentioning
confidence: 42%
“…We deployed CTs and automated scent dispensers in the North Cascades of Washington to detect wolverines, and in the Rocky Mountains of Idaho to detect fishers, as well as nontarget species in both regions. Surveys were conducted intensively in Washington (i.e., via a high density of stations in areas known to be used by wolverines; Aubry et al., 2023), and extensively in Idaho (i.e., at lower densities within a larger study area; Krohner et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations